The Future of Open Science: Unlocking Knowledge Together – Open Science Training - Nyirongo, Revelation (My University, 2023)
UbuntuNet Alliance under the AfricaConnect3 project invited 20 librarians to participate in a one-day Open Science training session a day before the UbuntuNet Connect 2023 Conference.
Keywords: Open Science; Open Science Training; Librarians